El art. 37, numeral 2 de la constitución de la República del Ecuador en relación al trabajo que realizan los adultos mayores - Palacios Cueva, Edwar Alfonso (2014)
The Constitution of the Republic of Ecuador in Article 37, paragraph 2 between one of the Rights of the Elderly, paid work, in order to their capabilities to the effect will be taken into account its limitations, but within the standard regulates the work is not properly regulated labor activity of this vulnerable group of society in relation to remuneration, compensation, working hours among others, therefore it is necessary within the legal framework set all necessary rules aimed at regulate the legal work and staff of the elderly people, who due to their economic needs have to perform an economic labor in order to lavish necessary for subsistence. Given the issues described above I decided to develop this research paper entitled: "THE OLDER WORK ABOUT THE CONSTITUTIONAL RULE CONTAINED IN ART. 37, NUMBER 2 OF THE CONSTITUTION OF THE REPUBLIC OF ECUADOR "in which I analyze legal doctrine and the issues raised, making demonstrate the failure of the law and the urgent need to regulate within the regulatory framework of the work as employees labor activity of this vulnerable group of society. Thus in this paper reflected the theoretical arguments, results of the field research, in which analysis demonstrates the need to regulate the work of the elderly within the law regulating the work in relation to remuneration, compensation, working hours among others, to enable better implementation of the constitutional provision in Article 37, paragraph 2, this being the main idea of my thesis, which I hope will help to solve this problem.